2022
DOI: 10.1155/2022/5194566
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Related Factors Affecting Facial Nerve Function after Acoustic Neuroma Surgery

Abstract: Objective. To investigate the factors affecting facial nerve function after acoustic neuroma surgery and to provide theoretical reference for clinicians to preserve facial nerve function better after surgery. Methods. A retrospective cohort study was conducted to analyze the correlation between postoperative facial nerve function and surgical approach, age, sex, tumor size and adhesion degree of facial nerve in 152 patients with acoustic neuroma. Results. In the choice of surgical approach, there was no signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…Los principales abordajes quirúrgicos para el neuroma auditivo son el abordaje por el seno sigmoideo posterior, el abordaje por la fosa craneal media y el abordaje por el vago. Según los informes de la literatura, los neurocirujanos actuales son buenos en el uso de la vía del seno retrosigmoide para la cirugía debido a su amplio ámbito de aplicación, la alta tasa de resección tumoral y el reconocimiento temprano de la vía del nervio facial (Liu et al,2022).…”
Section: Discussionunclassified
“…Los principales abordajes quirúrgicos para el neuroma auditivo son el abordaje por el seno sigmoideo posterior, el abordaje por la fosa craneal media y el abordaje por el vago. Según los informes de la literatura, los neurocirujanos actuales son buenos en el uso de la vía del seno retrosigmoide para la cirugía debido a su amplio ámbito de aplicación, la alta tasa de resección tumoral y el reconocimiento temprano de la vía del nervio facial (Liu et al,2022).…”
Section: Discussionunclassified
“…The degree of adhesion is a universally acknowledged critical risk factor of poor FN function [30] . Nonetheless, there are two problems with determining the adhesive degree: 1) identification criterion is so objective and different as it mainly depends on observation by the neurosurgeon with naked eyes during surgery [31] and 2) the FN is almost integrated anatomically with the mass as a wholly enhanced lesion on MRI, leaving unrecognizable intraoperative dissection plane [32] . However, the ROI delineation can segment the entire enhanced lesion with integrated FN.…”
Section: Discussionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%